Method for synergistically improving mechanical strength of lightweight aggregate concrete by using multiple solid wastes
By leveraging the synergistic effects of multiple solid wastes, and utilizing a composite of calcium silicate slag, waste ceramic materials, steel slag, zirconium silicate slag, and silica fume, combined with chemical activators, the problems of insufficient mechanical strength and hydration heat control in lightweight aggregate concrete have been solved. This has achieved a balance between high strength and low hydration heat, and promoted the large-scale utilization of industrial solid waste.
Patent Information
- Application Number
- CN202510927987.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-07-07
- Publication Date
- 2025-10-31
AI Technical Summary
Traditional lightweight aggregate concrete has insufficient mechanical strength, and the effect of adding a single solid waste to concrete is limited. It is difficult to simultaneously improve strength and control heat of hydration, which can easily lead to structural cracking, especially in large-volume concrete projects.
By employing the synergistic effect of multiple solid wastes, through the composite of calcium silicate slag, waste ceramic materials, steel slag, zirconium silicate slag and silica fume, combined with chemical activators, a synergistic enhancement mechanism is formed to improve the mechanical properties of concrete and reduce the heat of hydration.
It significantly improves the compressive and flexural strength of lightweight aggregate concrete, reduces the heat of hydration, achieves a balance between high strength and low heat of hydration, promotes the large-scale utilization of industrial solid waste, and meets the needs of high-rise buildings and large-volume projects.
Smart Images

Figure BDA0005485353950000081 
Figure BDA0005485353950000091
Abstract
Description
Technical Field
[0001] This invention belongs to the field of building materials technology, and more specifically relates to a method for synergistically improving the mechanical strength of lightweight aggregate concrete by multiple solid wastes. Background Technology
[0002] In the field of building materials, lightweight aggregate concrete is widely used due to its lightweight and heat-insulating properties. However, traditional lightweight aggregate concrete suffers from insufficient mechanical strength, especially in large-volume concrete projects. The large amount of heat generated during cement hydration can easily lead to excessive internal and external temperature differences, causing structural cracking and other defects. Furthermore, the large-scale stockpiling of industrial solid waste (such as calcium silicate slag, waste ceramic materials, steel slag, zirconium silicate slag, etc.) not only occupies land resources but also may cause environmental pollution. How to efficiently utilize these solid wastes and improve concrete performance has become an urgent problem to be solved.
[0003] In existing technologies, the effects of incorporating a single solid waste into concrete are limited and may negatively impact the workability or strength of the concrete. For example, using only steel slag or waste ceramic aggregates makes it difficult to simultaneously achieve strength improvement and heat of hydration control. Moreover, existing research has shown that increasing the amount of solid waste significantly reduces the mechanical strength and workability of concrete. Therefore, there is an urgent need for a method that utilizes the synergistic effect of multiple solid wastes to improve the mechanical strength of lightweight aggregate concrete while reducing the heat of hydration, thus solving the problem of the inability to simultaneously achieve high-performance concrete with high solid waste content. Summary of the Invention
[0004] The purpose of this invention is to provide a method for synergistically improving the mechanical strength of lightweight aggregate concrete by multiple solid wastes, so as to solve the problems existing in the prior art. Through the synergistic effect of multiple solid wastes, the mechanical strength of lightweight aggregate concrete is improved while its heat of hydration is reduced.
[0005] To achieve the above objectives, the present invention provides the following solution:
[0006] One of the technical solutions of this invention is to provide a high-strength lightweight aggregate concrete, which, by mass parts, comprises the following raw materials: 40-60 parts cement, 40-50 parts calcium silicate slag, 20-30 parts waste ceramic material, 20-30 parts steel slag, 20-30 parts zirconium silicate slag, 10-15 parts silica fume, 0.2-0.5 parts chemical activator, and 70-80 parts water;
[0007] The chemical activator is a composite system of sodium sulfate and calcium hydroxide in a mass ratio of 1:1 to 2.
[0008] Preferably, the particle size of the calcium silicate slag is ≥300 mesh; the particle size of the waste ceramic material is 0.05~0.08mm.
[0009] Preferably, the particle size of the steel slag is 8-12 mm; the particle size of the zirconium silicon slag is 60-100 μm.
[0010] Preferably, the particle size of the silica fume is 100–300 nm.
[0011] Preferably, the waste ceramic material is activated waste ceramic material; the preparation steps of the activated waste ceramic material include: immersing the waste ceramic material in a phosphoric acid solution and a silane coupling agent solution in sequence, and drying it to obtain the activated waste ceramic material.
[0012] Preferably, the phosphoric acid solution has a mass fraction of 4-8%; the silane coupling agent solution has a concentration of 1-2 wt%; the immersion time in the phosphoric acid solution is 1-2 h; and the immersion time in the silane coupling agent solution is 10-15 min.
[0013] Preferably, the steel slag is carbonized steel slag; the preparation steps of the carbonized steel slag include: curing the steel slag in a CO2 atmosphere for 24-48 hours.
[0014] Preferably, the silicon-calcium slag and the zirconium-silicon slag are calcined silicon-calcium slag and zirconium-silicon slag, respectively.
[0015] Preferably, the calcination temperature of the calcium silicate slag is 600-800℃ and the time is 1-2 hours; the calcination temperature of the zirconium silicate slag is 900-1000℃ and the time is 30-60 minutes.
[0016] The second technical solution of the present invention provides a method for preparing the above-mentioned high-strength lightweight aggregate concrete, comprising the following steps:
[0017] The cement, calcium silicate slag, waste ceramic material, steel slag, zirconium silicate slag, silica fume and water are mixed, and then a chemical activator is added to obtain high-strength lightweight aggregate concrete.
[0018] The technical mechanism of this invention is as follows:
[0019] This invention significantly improves the performance of the resulting concrete through the synergistic enhancement effect of multiple solid wastes.
[0020] Calcined calcium silicate slag is rich in CaO, SiO2, and Al2O3, and has a large specific surface area. In concrete, calcium silicate slag undergoes a pozzolanic reaction with the cement hydration product Ca(OH)2, generating additional CSH gel and CAH gel, which fill the pores of the cement paste and improve the matrix density. The slow-release effect of calcium silicate slag delays the hydration process, resulting in a more uniform distribution of gel products and reducing microcracks caused by rapid hydration.
[0021] The porous structure of waste ceramic aggregates slowly releases moisture during concrete hardening, forming an internal curing effect and promoting cement hydration in the later stages. Simultaneously, its high hardness provides rigid support to the matrix. Steel slag, as coarse aggregate, not only enhances the skeleton strength with its high density and high CaO content, but also forms chemical bonds with the hydration products of calcium silicate slag, improving the microstructure of the aggregate-cement stone interface transition zone (ITZ).
[0022] Zirconium silicate slag, as a fine aggregate, fills the pores of cement stone with its nano-sized particles, reducing porosity. Simultaneously, the presence of ZrO2 in the calcined slag acts as crystal nuclei, promoting the orderly growth of CSH gel, refining grains, and enhancing matrix strength. Furthermore, the active SiO2 in the calcined slag participates in the secondary hydration reaction, consuming Ca(OH)2 and reducing the directional arrangement of Ca(OH)2 crystals in the interfacial region, further strengthening the ITZ (Intense Iron-Zone).
[0023] Furthermore, the pozzolanic reaction rate of calcium silicate slag is lower than that of cement, thus delaying the peak hydration heat release. The high water absorption rate of waste ceramic materials and steel slag adsorbs moisture in the mixture, forming a water buffer layer that slows down the contact rate between cement particles and water, thereby reducing the hydration heat release rate. Pretreatment of calcium silicate slag increases its specific surface area, improves its reactivity, and results in more uniform heat release, preventing localized overheating.
[0024] The composite incorporation of calcium silicate slag and zirconium silicate slag reduces cement usage, lowering the total heat of hydration from the source. Simultaneously, it generates more CSH gel than traditional cement systems, and since the heat of hydration of CSH is lower than that of Ca(OH)2, it further reduces the total heat release. Silica fume can fill micropores, improve density, enhance the strength of the interfacial transition zone (ITZ), and react with cement hydration products to form CSH gel. Furthermore, it complements the active SiO2 in calcium silicate slag and zirconium silicate slag, improving the activation effect of the chemical activator (a composite system of sodium sulfate and calcium hydroxide).
[0025] This invention reduces the porosity of ITZ through the synergistic effect of multiple solid wastes, fills the pores of ITZ with the hydration products of calcium silicate slag, refines the crystal size with the micro-aggregate effect of zirconium silicate slag, and increases the mechanical interlocking with cement stone by the surface rough structure of waste ceramic materials and steel slag, ultimately forming a strong interface transition zone, which significantly improves the overall mechanical properties of concrete.
[0026] The present invention discloses the following technical effects:
[0027] (1) Significantly improved mechanical strength: Through the synergistic effect of calcium silicate slag, waste ceramic material, steel slag, zirconium silicate slag and silica fume, the compressive strength of high-strength lightweight aggregate concrete is improved compared with traditional lightweight aggregate concrete, and the flexural strength is improved, which meets the strength requirements of high-rise buildings and large-volume projects.
[0028] (2) Effective reduction of heat of hydration: The slow-release effect of calcium silicate slag and porous aggregate (waste ceramic material, steel slag) reduces the heat release of concrete hydration, slows down the hydration rate, and controls the internal and external temperature difference within 25℃, significantly reducing the risk of structural cracking.
[0029] (3) High utilization rate of solid waste: The total content of solid waste (silicon calcium slag, waste ceramic material, steel slag, zirconium silicon slag) in the raw materials reaches 60-70%, realizing the large-scale utilization of industrial solid waste, reducing production costs while meeting the requirements of green building materials development.
[0030] (4) Optimized construction performance: After the aggregate is treated to retain water, the workability of the concrete is good, the slump is maintained at 180-220mm, which facilitates the pouring and construction and reduces the shrinkage rate in the later stage. Detailed Implementation
[0031] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0032] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.
[0033] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.
[0034] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be readily apparent to those skilled in the art. This specification and embodiments are merely exemplary.
[0035] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.
[0036] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.
[0037] Unless otherwise specified, all raw materials used in this invention are commercially available products or solid waste obtained from local solid waste treatment plants.
[0038] Cement: Ordinary Portland cement PO42.5.
[0039] Calcium silicate slag: particle size ≥ 300 mesh; calcination steps: take calcium silicate slag and calcine it at 700℃ for 1 hour.
[0040] Waste ceramic material: particle size 0.08 mm; activation steps are as follows: take waste ceramic material, immerse it in a 4 wt% phosphoric acid solution for 1 hour, then take it out and dry it at 60°C, then immerse it in a 1 wt% methacryloyloxysilane solution for 15 minutes, take it out and dry it at 60°C to complete the activation; preparation steps of methacryloyloxysilane solution are as follows: dissolve a certain amount of methacryloyloxysilane in a mixed solution of ethanol and water with a volume ratio of 4:1 to obtain a 1 wt% methacryloyloxysilane solution.
[0041] Steel slag: particle size is 12mm; carbonization step is: the steel slag is cured in CO2 atmosphere (CO2 concentration is 40%) for 24h.
[0042] Zirconium silicon slag: particle size 80μm; calcination steps: take the zirconium silicon slag and calcine it at 900℃ for 30min.
[0043] Silica fume: Particle size 250nm.
[0044] Example 1
[0045] Preparation of high-strength lightweight aggregate concrete:
[0046] Prepare 50 parts cement, 40 parts calcium silicate slag, 20 parts waste ceramic material, 25 parts steel slag, 30 parts zirconium silicate slag, 10 parts silica fume, 0.5 parts chemical activator (a composite system of sodium sulfate and calcium hydroxide in a 1:1 mass ratio), and 70 parts water.
[0047] According to the above-mentioned dosage, cement, calcium silicate slag, waste ceramic material, steel slag, zirconium silicate slag, silica fume and water are placed in a mixer and mixed for 2 minutes. Then, a composite system of sodium sulfate and calcium hydroxide with a mass ratio of 1:1 is added and mixed evenly to obtain high-strength lightweight aggregate concrete.
[0048] Example 2
[0049] Preparation of high-strength lightweight aggregate concrete:
[0050] Prepare 40 parts cement, 45 parts calcium silicate slag, 20 parts waste ceramic material, 25 parts steel slag, 30 parts zirconium silicate slag, 10 parts silica fume, 0.5 parts chemical activator (a composite system of sodium sulfate and calcium hydroxide in a mass ratio of 1:2), and 70 parts water.
[0051] According to the above-mentioned dosage, cement, calcium silicate slag, waste ceramic material, steel slag, zirconium silicate slag, silica fume and water are placed in a mixer and mixed for 2 minutes. Then, a composite system of sodium sulfate and calcium hydroxide with a mass ratio of 1:2 is added and mixed evenly to obtain high-strength lightweight aggregate concrete.
[0052] Example 3
[0053] Preparation of high-strength lightweight aggregate concrete:
[0054] Prepare 50 parts cement, 50 parts calcium silicate slag, 20 parts waste ceramic material, 30 parts steel slag, 30 parts zirconium silicate slag, 15 parts silica fume, 0.5 parts chemical activator (a composite system of sodium sulfate and calcium hydroxide in a mass ratio of 1:2), and 70 parts water.
[0055] According to the above-mentioned dosage, cement, calcium silicate slag, waste ceramic material, steel slag, zirconium silicate slag, silica fume and water are placed in a mixer and mixed for 2 minutes. Then, a composite system of sodium sulfate and calcium hydroxide with a mass ratio of 1:2 is added and mixed evenly to obtain high-strength lightweight aggregate concrete.
[0056] Comparative Example 1 (small amount of calcium silicate slag)
[0057] The difference from Example 1 is that the amount of calcium silicate slag used is 25 parts, while the rest is the same as in Example 1.
[0058] Comparative Example 2 (without silica-calcium slag)
[0059] The difference from Example 1 is that the addition of calcium silicate slag is omitted, while the rest is the same as in Example 1.
[0060] Comparative Example 3 (without zirconium silicon slag)
[0061] The difference from Example 1 is that the addition of zirconium silicon slag is omitted, while the rest is the same as in Example 1.
[0062] Comparative Example 4 (Different Types of Lightweight Aggregate)
[0063] The difference from Example 1 is that lightweight ceramsite (particle size 10mm, water absorption rate 15%, cylinder compressive strength 6MPa) of equal mass is used to replace the combination of waste ceramic material, steel slag and zirconium silicon slag, while the rest is the same as in Example 1.
[0064] Comparative Example 5 (Different Cement Doses)
[0065] The difference from Example 1 is that the amount of cement is increased to 80 parts, and the amount of water is adjusted to ensure that the water-cement ratio remains unchanged. Otherwise, it is the same as Example 1.
[0066] Comparative Example 6 (Different Pretreatment Methods for Calcium Silicate Slag)
[0067] The difference from Example 1 is that the calcium silicate slag is dried only once, without ball milling and secondary drying, otherwise it is the same as Example 1.
[0068] Specifically, 30 portions of calcium silicate slag were placed in an oven and dried at 65°C for 6 hours. The dried calcium silicate slag was then crushed with a small hammer, passed through a 200-mesh square-hole sieve, and the material passing through the sieve was collected to obtain pretreated calcium silicate slag for later use.
[0069] Comparative Example 7 (without sodium sulfate)
[0070] The difference from Example 1 is that sodium sulfate is replaced with an equal mass of calcium hydroxide, otherwise the same as in Example 1.
[0071] Comparative Example 8 (without calcium hydroxide)
[0072] The difference from Example 1 is that calcium hydroxide is replaced with an equal mass of sodium sulfate, otherwise it is the same as Example 1.
[0073] Comparative Example 9 (Different Chemical Activators)
[0074] The difference from Example 1 is that the composite system of sodium sulfate and calcium hydroxide in a mass ratio of 1:1 is replaced with an equal mass of water glass with a modulus of 1.5, otherwise it is the same as Example 1.
[0075] Comparative Example 10 (without silica ash)
[0076] The difference from Example 1 is that the addition of silica fume is omitted, otherwise it is the same as Example 1.
[0077] Performance testing:
[0078] 1. Compressive strength and flexural strength tests: In accordance with GB / T 50081-2019 "Standard for Test Methods of Physical and Mechanical Properties of Concrete", the 150mm×150mm×150mm cube specimens were cured for 28 days and the compressive strength was tested using an electro-hydraulic servo pressure testing machine; the flexural strength of the 150mm×150mm×600mm prism specimens was tested.
[0079] 2. Hydration heat test: A non-contact calorimeter (TAMAir) was used to test the hydration heat release rate and cumulative heat release of the concrete mixture under a constant temperature of 30℃ for 72 hours.
[0080] 3. Water absorption and shrinkage test: Water absorption is tested according to GB / T 25189-2010; Shrinkage is tested using a horizontal concrete shrinkage meter, measuring the linear shrinkage within 28 days of standard curing.
[0081] The test results are shown in Table 1.
[0082] Table 1
[0083]
[0084]
[0085] As shown in Table 1, the mechanical properties of Examples 1-3 are significantly improved compared with Comparative Examples 1-10, proving that the synergistic effect of calcium silicate slag and multi-element aggregates significantly improves the strength; the strength of Comparative Examples 1 and 2 is significantly reduced due to insufficient or absent calcium silicate slag content.
[0086] Heat of hydration control: The cumulative heat release of Examples 1-3 was lower than that of Comparative Examples 1-10, especially Comparative Example 2, which had the highest heat release when there was no calcium silicate slag, indicating that the slow-release effect of calcium silicate slag is the key to reducing the heat of hydration.
[0087] Volume stability: The shrinkage and water absorption rates of Examples 1-3 were lower than those of Comparative Examples 1-10, indicating that the water-retaining aggregate and the silica-calcium slag pretreatment process effectively improved the impermeability and volume stability of concrete.
[0088] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.
[0089] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A high-strength lightweight aggregate concrete, characterized in that, The raw materials, by weight, include the following: 40-60 parts cement, 40-50 parts calcium silicate slag, 20-30 parts waste ceramic material, 20-30 parts steel slag, 20-30 parts zirconium silicate slag, 10-15 parts silica fume, 0.2-0.5 parts chemical activator, and 70-80 parts water. The chemical activator is a composite system of sodium sulfate and calcium hydroxide in a mass ratio of 1:1 to 2.
2. The high-strength lightweight aggregate concrete according to claim 1, characterized in that, The particle size of the calcium silicate slag is ≥300 mesh; the particle size of the waste ceramic material is 0.05~0.08mm.
3. The high-strength lightweight aggregate concrete according to claim 1, characterized in that, The steel slag has a particle size of 8–12 mm; the zirconium-silicon slag has a particle size of 60–100 μm.
4. The high-strength lightweight aggregate concrete according to claim 1, characterized in that, The particle size of the silica fume is 100–300 nm.
5. The high-strength lightweight aggregate concrete according to claim 1, characterized in that, The waste ceramic material is activated waste ceramic material; The preparation steps of the activated waste ceramic material include: immersing the waste ceramic material in a phosphoric acid solution and a silane coupling agent solution in sequence, and drying it to obtain the activated waste ceramic material.
6. The high-strength lightweight aggregate concrete according to claim 5, characterized in that, The phosphoric acid solution has a mass fraction of 4-8%; the silane coupling agent solution has a concentration of 1-2 wt%; the immersion time in the phosphoric acid solution is 1-2 h; and the immersion time in the silane coupling agent solution is 10-15 min.
7. The high-strength lightweight aggregate concrete according to claim 1, characterized in that, The steel slag is carbonized steel slag; The preparation steps of the carbonized steel slag include: curing the steel slag in a CO2 atmosphere for 24 to 48 hours.
8. The high-strength lightweight aggregate concrete according to claim 1, characterized in that, The silicon-calcium slag and zirconium-silicon slag are respectively calcined silicon-calcium slag and zirconium-silicon slag.
9. The high-strength lightweight aggregate concrete according to claim 8, characterized in that, The calcination temperature of the silicon-calcium slag is 600-800℃, and the time is 1-2 hours; the calcination temperature of the zirconium-silicon slag is 900-1000℃, and the time is 30-60 minutes.
10. The method for preparing high-strength lightweight aggregate concrete according to any one of claims 1 to 9, characterized in that, Includes the following steps: The cement, calcium silicate slag, waste ceramic material, steel slag, zirconium silicate slag, silica fume and water are mixed, and then a chemical activator is added to obtain high-strength lightweight aggregate concrete.